The Implications of the Tijaniyah Order for Islamic Education at Zawiyah Islamic Boarding School - Aji Muhammad Ikbal; Ahmad Nurwadjah; Andewi Suhartini (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2023)
This study aims to determine the implementation of the Tijaniyah Order at the Zawiyah Islamic Boarding School and the implications of the Tijaniyah Order for Islamic Education in a portrait from the point of view of achieving the goals of Islamic education at the Islamic Boarding School. The method used is qualitative with a case study approach. Data collection techniques were carried out using interviews and documentation. Data analysis uses miles and Huberman models. As well as the validity test using the credibility test (credibility) with the triangulation method. The results showed that the implementation of the Tijaniyah Order at the Zawiyah Islamic Boarding School was carried out by; 1) maintaining the syari'at through riyadah and tajkiyatunnafs, 2) building personal istiqamah through practising practice practising wirid. So that the educational process at the Zawiyah Islamic Boarding School has its peculiarities where the learning process not only transfers knowledge but is accompanied by carrying out the teachings of the Tijaniyah order as a form of riyadah in shaping the personality of the students. This was done to realize the goals of Islamic education to build physical education, spiritual education, and intellectual education in creating the profile of students at Zawiyah Islamic Boarding School.